Tinjauan Kuantitatif Mutu Rekam Medis pada Formulir Discharge Summary Rawat Inap - Ibrahim, Mochammad Malik (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2024)
Quality medical records are the responsibility of health workers who fill out medical record files, analyzing the quality of medical records must be done to ensure the completeness of the contents of medical records, indicators that affect the quality of medical records, namely completeness, accuracy, legal aspects, and accuracy of returning medical records. The purpose of this study was to identify the quality of medical records on the inpatient discharge summary form. The research method used a descriptive quantitative cross-sectional approach, the research instrument used a checklist sheet. The results obtained in the completeness indicator are 70.0% unfilled medical history items, 67.3% inaccurate accuracy indicators, 60.7% incomplete DPJP signature legal aspect indicators and 33.3% inappropriate return timeliness indicators. It is concluded that there is still incompleteness in the inpatient discharge summary section, this is closely related to the quality indicators of medical records and there is an untimely return of medical record files, so the researcher hopes that there will be a special SOP for the discharge summary, giving rewards to officers who fill in completely and return medical record files on time.